Maus : - Spiegelman, Art (Pantheon Books, 1997)
It is the story of Vladek Speigelman, a Jewish survivor of Hitler's Europe, and his son, a cartoonist coming to terms with his father's story. Maus approaches the unspeakable through the diminutive. Its form, the cartoon (the Nazis are cats, the Jews mice), shocks us out of any lingering sense of familiarity. Maus is a haunting tale within a tale. Vladek's harrowing story of survival is woven into the author's account of his tortured relationship with his aging father. Against the backdrop of guilt brought by survival, they stage a normal life of small arguments and unhappy visits. This astonishing retelling of our century's grisliest news is a story of survival, not only of Vladek but of the children who survive even the survivors. Maus studies the bloody pawprints of history and tracks its meaning for all of us.